2012
DOI: 10.1111/j.1468-2427.2012.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft Spaces, Fuzzy Boundaries and Spatial Governance in Post‐devolution Wales

Abstract: This article explores the responses of senior local government actors to the 2004 Wales Spatial Plan and its 2008 update. An example of the so‐called ‘new spatial planning’ which has emerged in the movement towards regional devolution in the UK, this planning discourse foregrounds elements of relational thinking that seek to alternatively augment, destabilize and overturn orthodox administrative categories and divisions of space. Whereas spatial planners have traditionally thought and practised with and throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 46 publications
1
66
0
2
Order By: Relevance
“…An attempt to produce a more nuanced and process-led representation of Wales's internal geography was made with the Wales Spatial Plan in 2004 (updated in 2008), but subsequent efforts to align the initially 'fuzzy' boundaries of the spatial plan regions with the hard boundaries of local authority areas demonstrates the accretional power of fixed institutional geographies in shaping the representation of localities (cf. HAUGHTON et al, 2010;HELEY, 2012;HELEY and JONES, 2012b;WELSH ASSEMBLY GOVERNMENT, 2004. 4 The Knowing Localities Research Programme was designed to develop understanding of the form and effects of localities in Wales.…”
Section: Doing 'New Localities' Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt to produce a more nuanced and process-led representation of Wales's internal geography was made with the Wales Spatial Plan in 2004 (updated in 2008), but subsequent efforts to align the initially 'fuzzy' boundaries of the spatial plan regions with the hard boundaries of local authority areas demonstrates the accretional power of fixed institutional geographies in shaping the representation of localities (cf. HAUGHTON et al, 2010;HELEY, 2012;HELEY and JONES, 2012b;WELSH ASSEMBLY GOVERNMENT, 2004. 4 The Knowing Localities Research Programme was designed to develop understanding of the form and effects of localities in Wales.…”
Section: Doing 'New Localities' Researchmentioning
confidence: 99%
“…1 The paper does not discuss the research programme or its findings in detail HELEY, 2012;HELEY and JONES, 2012b;HELEY and MOLES, 2012), but rather it seeks to move from the particular to the general and highlights how principles from the 'new localities' approach have been engaged to allow meaningful representations of 'locality' to be constructed and mobilized through the research.…”
Section: Introductionmentioning
confidence: 99%
“…Elements of this framework have been proposed and used in literature (Heley, 2013;Hernes, 2004;Schut et al, 2013;Sternlieb et al, ~ 165 ~ 2013;Van Broekhoven et al, 2014), but the framework as a whole is new. Its cyclical nature allows the study of multiple cycles of boundary management as have been identified in the case studies.…”
Section: Contribution To Scientific Debatementioning
confidence: 99%
“…Negotiations and conflicts about these boundaries are at the heart of spatial planning and governance. A complicating matter is that 'areas' and categories of land use, when delineated spatially, may not match the administrative and ownership boundaries (Boonstra and Van Den Brink, 2007;Cash et al, 2006;Heley, 2013;Padt and Westerink, 2012). Administrative and ownership boundaries have received wide attention in literature.…”
Section: Boundaries In Spatial Governance: Institutional Social and mentioning
confidence: 99%
See 1 more Smart Citation